Analisis Elemen Pariwisata Kawasan Wisata Danau Sebedang - Kharisma, Antonius Hansen; Firmansyah, Ade; Mukhlis, Andi M. Ahsan (SPECTA Journal of Technology, 2024)
Tourism development is generally directed towards leading sectors that can boost economic growth, increase local revenue, and expand job opportunities. One form of tourism that is being developed is nature-based tourism, namely lakes. Sebedang Lake is a natural tourism object included in the National Tourism Strategic Area (KSPN) for Sambas Regency and its surroundings. Sebedang Lake is also the only natural lake along the northern coast of West Kalimantan. This research aims to analyze the tourism aspects of Sebedang Lake. In identifying existing conditions in the Lake Sebedang area, there are several identification activities including attractions, amenities, accessibility, accommodation, and the stakeholders involved. The research method used is a qualitative approach using descriptive analysis with data collection techniques in the form of observation, interviews, field notes, personal documentation, spatial analysis, and other official documents. An analysis of Sebedang Lake's tourism development reveals several shortcomings. Attractions and activities cluster near the main access, neglecting the broader area's potential. Amenity distribution suffers a similar imbalance, leaving vast stretches underserved. Accommodation options are limited to just two villas/homestays. While the main access road boasts good condition and high accessibility, inadequate lighting hampers safety. Furthermore, unpaved pathways to activity points pose an inconvenience. Stakeholder involvement includes the Sambas Regency Tourism Office,Pokdarwis, and local communities, each playing their part.